2005
DOI: 10.1021/ma0476792
|View full text |Cite
|
Sign up to set email alerts
|

An Orientationally Ordered Hierarchical Exfoliated Clay−Block Copolymer Nanocomposite

Abstract: Creation of an orientationally ordered hierarchical nanocomposite can be done by the preferential insertion of individual polymer-covered clay layers into block copolymer (BCP) microdomainsin the present instance, PS-functionalized silicate layers into the polystyrene (PS) domains of a styrene−butadiene−styrene triblock copolymer (SBS). We present here the method required to achieve such an ordered block copolymer−nanoparticle composite and report preliminary mechanical properties. PS is grafted-to or polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 39 publications
5
71
2
Order By: Relevance
“…50 The most interesting phenomenon they studied was the se- brushes (MMT-PS) and once again found selective segregation into PS domains. 51 Although domain deformation to accommodate MMT-PS particles was much greater with MMT-PS than with Au-PS, the lamellar morphology persisted thanks to the compatibility of MMT plate-like geometry with the lamellar structure. The three dimensional matching of nanoparticle geometry with BCP domain geometry is known as symmetry matching and is an important consideration to develop useful nanocomposites.…”
Section: Block Copolymer Nanocompositesmentioning
confidence: 98%
See 3 more Smart Citations
“…50 The most interesting phenomenon they studied was the se- brushes (MMT-PS) and once again found selective segregation into PS domains. 51 Although domain deformation to accommodate MMT-PS particles was much greater with MMT-PS than with Au-PS, the lamellar morphology persisted thanks to the compatibility of MMT plate-like geometry with the lamellar structure. The three dimensional matching of nanoparticle geometry with BCP domain geometry is known as symmetry matching and is an important consideration to develop useful nanocomposites.…”
Section: Block Copolymer Nanocompositesmentioning
confidence: 98%
“…The use of block copolymers in NCPs to date has been largely limited to a supporting matrix for the suspension of homopolymer functionalized inorganic fillers. [50][51][52] The most prevalent method has been the grafting of polystyrene to montmorillonite and solvent blending with a compatible block copolymer; BCP morphology in these cases is nearly always lamellar. The simple blending of clays with block copolymers has not yet yielded any greater degree of control of particle distribution than traditional homopolymer nanocomposites.…”
Section: Block Copolymer Nanocompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ha et al reported that PS-tethered Cloisite clay particles, which were exfoliated within a styrene-butadiene-styrene (SBS) block copolymer matrix and oriented using a rollcasting technique, templated the SBS morphology 20 . This clay platelet-induced morphology disrupted the alignment of the lamellar microdomains, resulting in minimal improvement in in-plane mechanical properties.…”
mentioning
confidence: 99%